Equal access to hospital care for children with learning disabilities and their families: a mixed-methods study - Kate Oulton; Jo Wray; Charlotte Kenten; Jessica Russell; Lucinda Carr; Angela Hassiotis; Carey Jewitt; Paula Kelly; Sam Kerry; Irene Tuffrey-Wijne; Mark Whiting; Faith Gibson (NIHR Journals Library, 2022)
Background: To our knowledge, there has yet to be a comprehensive review of how well hospital services are meeting the needs of children and young people (hereafter referred to as children) with learning disability and their families. The extent to which their experiences differ from those of parents of children without learning disability is not known. The views and experiences of children with learning disability are almost non-existent in the literature. Aims: To identify the cross-organisational, organisational and individual factors in NHS hospitals that facilitate and prevent children with learning disability and their families receiving equal access to high-quality care and services, and to develop guidance for NHS trusts. Design: A four-phase transformative, mixed-methods case study design comparing the experiences of children with and children without learning disability, their parents and health-care staff. Methods: Phase 1 comprised interviews with senior managers (n = 65), content analysis of hospital documents and a staff survey (n = 2261) across 24 hospitals in England, including all specialist children's hospitals. Phases 2-4 involved seven of these hospitals. Phase 2 involved (a) interviews and photography with children and their parents (n = 63), alongside a parent hospital diary and record of safety concerns; (c) hospital staff interviews (n = 98) and community staff survey (n = 429); and (d) retrospective mapping of hospital activity. During phase 3, children (n = 803) and parents (n = 812) completed satisfaction surveys. Phase 4 involved seeking consultation on the findings. Data analysis: A model for mixed-methods data analysis and synthesis was used. Qualitative data were managed and analysed thematically, supported with NVivo (QSR International, Warrington, UK). Quantitative data were analysed using parametric and non-parametric descriptive statistics. Results: Nationally, there is considerable uncertainty within hospitals and variation between hospitals in terms of the policies, systems and practices in place specifically for children with learning disability. Staff are struggling to individualise care and are being let down by an inadequate system. Attitudes and assumptions can have a lasting impact on parents and children. The findings serve as a useful guide to trusts about how best to meet the Learning Disability Improvement standards that have been set. Conclusions: Safety issues and quality of care affect all children in acute hospitals and their parents, but the impact on children with learning disability and their parents is much greater. Individualising care is key. Our findings suggest that staff may need to undertake training and gain experience to build their skills and knowledge about children with learning disability generally, as well as generate knowledge about the individual child through proactively working in partnership with parents before their child's admission. The findings also suggest that we may need to address the impact of children's hospitalisation on parents' health and well-being. Future work: The greatest need is for the development and validation of an instrument for the assessment and management of risk in children with learning disability in hospital. Limitations: We cannot say with certainty that the sites selected are representative of all services caring for children with learning disability. Study registration: The study has been registered on the National Institute for Health and Care Research (NIHR) Clinical Research Network portfolio as 20461 (phase 1) and 31336 (phases 2-4). Funding: This project was funded by the NIHR Health and Social Care Delivery Research programme and will be published in full in Health and Social Care Delivery Research; Vol. 10, No. 13. See the NIHR Journals Library website for further project information.